CONTRASTIVE RHETORIC ANALYSIS OF METADISCOURSE MARKERS OF THE PHILIPPINE AND INDONESIAN NEWSPAPER EDITORIALS - Djonda, Ubaldus (Universitas Muhammadiyah Metro, 2022)
This paper describes a contrastive study of the Philippine and Indonesian newspaper editorials in order to see similarities and differences in their physical size in terms of words and how Filipino and Indonesian editorialists utilized their discourse strategies through metadiscourse markers. To this end, 30 editorials of the Philippine Daily Inquirer and the Jakarta Post were examined through the lens of contrastive rhetoric analysis. The investigation of metadiscourse devices was grounded on the metadiscourse framework of Hyland (2005). Regarding the length of the editorials, the data revealed that the Philippine editorials employed more words compared to the Indonesian ones. The findings also show that both groups of editorialists used more interactional category, especially subcategory attitude markers in their writing, although the frequencies of the counts were different. The Philippine editorials contain more metadiscourse markers in all subcategories compared to the Indonesian editorials. The findings may indicate that as a genre, newspaper editorials have a generic feature of metadicourse markers, namely attitude markers. By using attitude markers effectively, editorialists make clear their stance on particular public issues and try to persuade readers to accept the opinion of the newspaper editors. The study shows that newspaper editorials are reader-oriented texts.